Process development for maximum Lycopene production from selected fruit waste - Jamal, Parveen; Akbar, Iqrah; Jaswir, Irwandi; Hashim, Yumi Zuhanis Has-Yun (2015)
Lycopene, one of the most widely used carotenoid is an efficient antioxidant and singlet oxygen quencher. The increasing demand of lycopene in the nutraceutical and drug industry has directed the researchers to produce lycopene with cost effective methods in a large scale to meet the growing demand. Thermal processing liberates this carotenoid from complexes with proteins, thus increasing its bioaccessibilty. The comparison of lycopene content was evaluated amongst fruit peels of guava, papaya, watermelon and red dragon fruit, in order to choose the best source. Lycopene content was measured using both UV–vis spectrophotometer and identified using high performance liquid chromatography (HPLC). Papaya, a tropical fruit showed tremendous potential as an alternative source and was selected to conduct further investigation. Response surface methodology (RSM) using faced centered central composite design (FCCCD) was applied to study the interaction between the most contributing factors i.e. temperature, time and solid-solvent ratio. From the results, themaximum lycopene yield of 103.1 mg/kg at temperature (1200C), time (5 hours) in a solid-solvent ratio of 1:40 g/mL were selected. The lycopene oleoresin was further purified by saponification and identified using HPLC, thus revealing that the major constituents of the lycopene oleoresin after saponification were lycopene and β- carotene which constitute 69.879% and 30.12% of the total oleoresin respectively.